Investigating Self-Regulated Learning Differences Based on Gender, Scholarship, and Student’s Housing - Nurdian Susilowati; Sari Lestari; Dela Yuniarsih; Deviana Hardining Maharani (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
This study aims to determine the differences students’ self-regulated learning (SRL) based on gender, scholarship, and student’s housing. Referring to Roscoe, our sample of the study is 36 students by using purposive sampling technique.. Analysis of the data are quantitative descriptive and hypothesis testing using independent sample t-test. The results showed that there is no significant difference in self-regulated learning based on gender. Self-regulated learning of female is higher than male students. Based on scholarships, there is no significant difference in self-regulated learning but students as scholarship recipients have higher self-regulated learning.Then, there is no significant difference based on house hold but students who live at home have highest self-regulated learning than students who live in boarding schools and boarding house. This research gives implication theoretically and practically. The finding proves that students who have self-regulated learning higher than others is due to good habit and intrinsic motivation. Thus; this research suggestsfor the university to establish good environment for students to develop themselves.